1996
DOI: 10.1093/tropej/42.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive smoking on frequency of respiratory illnesses and serum immunoglobulin-E (IgE) and interleukin-4 (IL-4) concentrations in exposed children

Abstract: We studied the relationship of serum immunoglobulin-E (Ig-E) and interleukin-4 (IL-4) concentrations, eosinophil counts, and frequency of respiratory illness with passive smoking in 70 randomly selected children of smoking parents. Fifty randomly selected age-matched children of non-smoking parents served as controls. Children of smoking parents had higher frequency of respiratory illnesses per year (P < 0.01), significantly higher total leucocytic and eosinophil counts, higher percentage of eosinophils (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…The immunomodulatory effect of tobacco smoke and its components have been well documented (Thomas et al, 1975;Ronchetti et al, 1990;Stone, 1992;Sopori et al, 1993;Abrams, 1995;Geng et al, 1995;El-Nawawy et al, 1996;Geng et al, 1996;Oryszczyn et al, 2000;Gilliland et al, 2001). In our previous studies we showed that prolonged exposure of OVA sensitized mice to ETS resulted in enhanced levels of serum IgE, IgG1, and blood eosinophils .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The immunomodulatory effect of tobacco smoke and its components have been well documented (Thomas et al, 1975;Ronchetti et al, 1990;Stone, 1992;Sopori et al, 1993;Abrams, 1995;Geng et al, 1995;El-Nawawy et al, 1996;Geng et al, 1996;Oryszczyn et al, 2000;Gilliland et al, 2001). In our previous studies we showed that prolonged exposure of OVA sensitized mice to ETS resulted in enhanced levels of serum IgE, IgG1, and blood eosinophils .…”
Section: Discussionmentioning
confidence: 69%
“…Epidemiological studies have concluded that exposure to ETS is responsible for some forms of cancer, respiratory disease and may also exacerbate the allergic response (Martinez et al, 1988;Stone, 1992;El-Nawawy et al, 1996;Gilliland et al, 2001). Studies on human subjects are rarely able to focus on ETS alone due to concurrent exposure to other environmental pollutants (such as ozone, diesel exhaust) which may also modulate the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether there were 11 cross-sectional studies, 5 7 19–30 4 prospective cohort studies4 6 31–34 and 4 case-control studies. 10 35–37 The studies were conducted in various regions of the world. The included subjects were aged 0–17 years.…”
Section: Resultsmentioning
confidence: 99%
“…The limited existing data on passive smoking and its direct effects on immune responses and respiratory health in children seem to confirm these observations 10–12. Therefore, our aim was to systematically review and update data from cross-sectional and cohort studies regarding the effect of ETS on serum total immunoglobulin E (tIgE) and specific IgE (sIgE) and skin-prick tests (SPTs), since they are easily assessable and objective markers of allergic sensitisation in children 13…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, the role of gender as a factor in the development of allergic asthma and particularly in allergic enhancement by environmental tobacco smoke (ETS) exposure has not been well examined. Although, a genetic predisposition to the development of allergic asthma is recognized (Daniels et al, 1996;Gern et al, 1999) evidence strongly suggests that environmental agents such as ETS increase its phenotypic expression (el-Nawawy et al, 1996;Gilliland et al, 2001). Some studies have shown that males are more likely to be allergic from exposure to ETS or mainstream smoke than females (Ronchetti et al, 1992;Omenaas et al, 1994;Jarvis et al, 1995), while others have reported no sex differences in the prevalence of allergy (Osaka et al, 1985).…”
Section: Introductionmentioning
confidence: 99%